O uso do experimento de termologia no ensino de Física: a curva de aquecimento da água - Rosa, Ricardo Silva (2018)
As a physics teacher since 2010 and observing the students’ difficulty, it was necessary to present them another teaching proposal, different from the traditional one with chalk and blackboard. Thus, an experimental class was used to verify the process of the water heating curve through a temperature x time graph, by using a computer worksheet and an experimental kit with the Arduino platform. The teaching methodology used was the experimentation that was chosen because of the great potential of attractiveness of it, always aiming at the involvement and participation of the students in class. As teaching theory, Lev Vigotski was used due to the comparison of the lessons to his studies of internalization. First it was expected that the students could read the graph mathematically, identifying the behavior of the related function that represents it and its coefficients, because when there is a temperature variation between zero and one hundred degrees Celsius, the graph formed is a line of non-zero angular coefficient. In a second moment, it is expected that the students could predict and calculate the values of the curve, such as boiling point, amount of heat in all moments of the curve, thermal power of the candle flames, etc. In a third moment, the students analyzed if the learning was profitable in front of the type of traditional classes they were accustomed in day by day; if through the experimental class, they could be more engaged and notice this in colleagues. With this work, it was possible to verify the great acceptance and need for experimental classes, which make a lot of difference in order to have a more engaging teaching that achieve students’ interest.